LEGAL CERTAINTY ON BUILDING DISTRIBUTION AND CONFORMITY WITH THE DETAILED SPATING PLAN IN THE WILDLAND OF MENGWI SPECIFICALLY IN THE GREEN OPEN SPACE ZONE AND THE AGRICULTURAL ZONE (ANALYSIS OF LEGAL CERTAINTY FOR BUILDINGS THAT VIOLATE SPATIAL PLANNING) - Darmayanti, Ni Putu Eka; Wiratny, Ni Ketut; Sihotang, Erikson (Ridwan Institute, 2024)
This study aims to identify and understand in depth the factors that cause development in the green open space zone and agricultural zone in Mengwi District, Badung Regency, as well as analyze the legal certainty for building owners in these zones. The research was carried out in a qualitative descriptive manner with legal interpretation and legal communication methods, which systematically prepared legal materials to be presented in the thesis entitled